Radial Joints Behavior of a Precast Asymmetric Underpass Induced by Long-Term Loads of Ground Vehicles - Zhiyi Jin; Taiyue Qi; Xiao Liang; Bo Lei; Yangyang Yu; Yuchen Gong; Weidu Ji (Shock and Vibration)
With the rapid development of the urbanization, many underpasses are designed and constructed in big cities to alleviate the huge traffic pressure. The construction method has been changed from traditional on-site concrete pouring technology to prefabricated assembly technology. However, this change will inevitably bring out some new problems to be studied such as the behaviour of the radial joints. In this study, the numerical simulation model of Moziqiao precast and assemble underpass with large asymmetric cross section was constructed by using the ABAQUS software to study the transient response of the underpass induced by ground surface dynamic load. Based on the similarity theory a 1/10 scaled model test was carried out to study the long-term radial joint behaviour of the underpass considering the prestress loss during the 2000 000 loading cycles. The results transient dynamic response from computed and tested was compared in terms of acceleration. The comparison showed that the transient response accelerations have good consistency. The results of the physical model test were analysed in terms of joint opening, closure, and slipping. The accumulative joint opening was closely correlated to the prestress level, and the joint opening at different prestress levels increased with the loss of the prestress. The joints closure decreased with the increase of the previous accumulative color value. The joint slipping mainly attributed to the slipping of the top segment. Both the opening and slipping of the joints at RJ 1 were larger than that of RJ3 due to the wider span of RJ1, which reflected an asymmetric effect. This study revealed the long-term accumulative behaviour of the radial joints, which convinced us that the long-term accumulative deformation of the joints should be taken into consideration during the design stage for similar projects.